2019
DOI: 10.5194/acp-2019-96
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Photochemical aging of atmospherically reactive organic compounds involving brown carbon at the air-aqueous interface

Abstract: <p><strong>Abstract.</strong> Photosensitizing compounds containing brown carbon can absorb UV light and transfer that energy to low volatile organic compounds at the surface of aqueous particles. To better understand the reactivity and photochemical aging processes of organic coating on the aqueous aerosol surface, we have simulated the photosensitized reaction of organic films made of several long chain fatty acids in a Langmuir trough in the presence or absence of i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…Many previous studies showed that photosensitized chemistry may be an important pathway for promoting the oxidation of VOCs (Kaur et al., 2019; Li et al., 2019a) in atmospheric particles, which can increase the mass of SOA. For example, irradiation of imidazole‐2‐carboxaldehyde (IC) and humic acid in the presence of various gaseous VOCs, such as d‐limonene, has been shown to produce highly oxygenated compounds and thereby initiate aerosol growth by photosensitized mechanisms (Aregahegn et al., 2013; González Palacios et al., 2016; Monge et al., 2012; Rossignol et al., 2014; Tsui et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many previous studies showed that photosensitized chemistry may be an important pathway for promoting the oxidation of VOCs (Kaur et al., 2019; Li et al., 2019a) in atmospheric particles, which can increase the mass of SOA. For example, irradiation of imidazole‐2‐carboxaldehyde (IC) and humic acid in the presence of various gaseous VOCs, such as d‐limonene, has been shown to produce highly oxygenated compounds and thereby initiate aerosol growth by photosensitized mechanisms (Aregahegn et al., 2013; González Palacios et al., 2016; Monge et al., 2012; Rossignol et al., 2014; Tsui et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Both sulfate and secondary organic aerosol (SOA) significantly impact air quality, climate, as well as human and ecosystem health (Fuzzi et al, 2015;Nel, 2005). Despite extensive research spanning nearly a century, we still do not fully understand all possible pathways for their formation and transformation in the atmosphere (Wang et al, 2014;Zhang et al, 2007).Many previous studies showed that photosensitized chemistry may be an important pathway for promoting the oxidation of VOCs (Kaur et al, 2019;Li et al, 2019a) in atmospheric particles, which can increase the mass of SOA. For example, irradiation of imidazole-2-carboxaldehyde (IC) and humic acid in the presence of various gaseous VOCs, such as d-limonene, has been shown to produce highly oxygenated compounds and thereby initiate aerosol growth by photosensitized mechanisms (…”
mentioning
confidence: 99%
“…Collins et al 441 observed the similar formation of oxygenated products when the lipid diacylglycerol phosphatidylcholine was exposed to UV radiation in the presence of docosahexaenoic acid as a photosensitizer. The work of Li et al 440 is unique because they not only used traditional model photosensitizers like IC and humic acid, they also used chambermade SOA and ambient PM 2.5 (particular matter with diameter <2.5 mm). SOA was generated from the photo-oxidation of limonene in the presence of OH, NO x , and ammonium sulfate seed particles.…”
Section: Phospholipidsmentioning
confidence: 99%
“…Similar results were obtained with these more complex photosensitizers as has been observed with IC and humic acid. The Li et al 440 study marks the rst time SOA and PM 2.5 were tested as photosensitizers for reactions of organic Langmuir lms.…”
Section: Phospholipidsmentioning
confidence: 99%
See 1 more Smart Citation